'Stability' of Assessment: Extending the Utility Equation - Tarun Sen Gupta; Eugene Wong; Deepak Doshi; Richard Hays (MedEdPublish, 2021)
The COVID-19 pandemic has brought many challenges to medical education, necessitating a rapid transition to digital delivery. The widespread move to online exams has introduced novel risks, including the risk of catastrophic IT failure. These are not ‘black swan’ events – something so unexpected and devastating that we could not anticipate them and prepare accordingly. The phrase ‘black elephants’, a cross between a black swan and ‘the elephant in the room’ has been coined to describe these events.